Comparison of Intravenous Administration of Remifentanil with Fentanyl for Increased Blood Sugar Levels in Post Cardiac Surgery Patients - Irvan; Tavianto, Doddy; Sudjud, Reza Widianto (Faculty of Medicine-Universitas Airlangga, 2024)
Introduction: The incidence of hyperglycemia in patients with heart disease undergoing cardiac surgery reaches 50% in patients without a history of Diabetes Mellitus. This condition of hyperglycemia can increase morbidity and mortality. Objective: This study aims to assess the effect of using the agent remifentanil intravenously 0.5-1 µg/kgBW bolus followed by maintenance at a dose of 0.05-0.1 µg/kgBW/minute intravenously compared to the use of fentanyl 3-10 µg/kgBW followed by a maintenance dose of 0.03-0.1 µg/kgBW/minute for increased blood sugar levels in patients undergoing cardiac surgery with the Cardiopulmonary Bypass (CPB) procedure. Methods: This study is an experimental study with a single-blind randomized controlled design. Patients will be divided into 2 groups consisting of 12 patients each, namely group R (remifentanil) received remifentanil, and group F (fentanyl) received fentanyl. Blood sugar levels will be checked before and after surgery. Results: The research has been conducted at Dr. Hasan Sadikin Hospital Bandung from February 2023 to May 2023. The average increase in blood sugar levels in the remifentanil group was 74 mg/dl, while in the fentanyl group, it was 90 mg/dl. The p-value given is 0.214. Statistical test results showed that the value of p> 0.05. Conclusion: This study concludes that there is no significant difference in the increase in blood sugar levels between the two groups (remifentanil and fentanyl). This can be caused by the use of opioid doses in the lower range and more complex surgical procedures in our research.